An introduction to mathematical cryptography - Hoffstein, Jeffrey; Pipher, Jill Catherine , 1955-; Silverman, Joseph H. , 1955- (Undergraduate texts in mathematics, 2008)
"This self-contained introduction to modern cryptography emphasizes the mathematics behind the theory of public key cryptosystems and digital signature schemes. The book focuses on these key topics while developing the mathematical tools needed for the construction and security analysis of diverse cryptosystems. Only basic filter algebra is requited of the reader; techniques from algebra, number theory, and probability are introduced and developed as required." "This book is an ideal introduction for mathematics and computer science students to the mathematical foundations of modern cryptography. The book includes an extensive bibliography and index; supplementary materials are available online."--BOOK JACKET